SUSTAINABLE (RE)DEVELOPMENT OF TOURISM DESTINATIONS AS A PLEDGE FOR THE FUTURE – A CASE STUDY FROM THE WESTERN BALKANS - Miroslav KNEŽEVIĆ; Renata PINDŽO; Milan ĆULIĆ; Sanja KOVAČIĆ; Milosav DUNJIĆ; Aleksandra VUJKO (Geo Journal of Tourism and Geosites)
The study aims to analyse and thus obtain a comprehensive understanding of the current situation, issues, needs, and challenges related to the tourism sector in the five Western Balkans economies in the post-COVID-19 context. The survey collects and analyze information for each of the five Western Balkans economies and explores the needs and trends of the current stakeholders in the tourism sector and how sustainable tourism can be used to overcome future uncertainties. The results are further discussed from the point of Western Balkans economies and tourism destination to make their management more sustainable for the future. Western Balkans countries have the potential for sustainable tourism development, but to better position themselves in the tourist market, they need to achieve a competitive advantage. Bearing in mind the changes that occurred during and after the crisis, it is necessary to have a good plan for the re(development) of tourist destinations.